Customer Satisfaction in Indigenous Telecommunication Companies In Nigeria: Role Of Service Quality - Adedayo Olufemi, Ogunberu; Omolade Sunday, Adeyemi; Timilehin Olasoji, Olubiyi; Adekunle Oluwole, Binuyo; Olajide-Arise, Temi (Syntax Corporation, 2024)
The Nigeria's telecommunication sector is strongly impacted by customer satisfaction and more so the sector is a competitive landscape where key companies (MTN, GLO, AIRTEL, and 9MOBILE) are vying to maintain their market share, ensure consumer satisfaction, and cultivate enduring service quality. Service quality is a major factor in determining customer satisfaction, especially in relation to mobile services offering, network reliability, data speed, and coverage. Therefore, this study examined service quality and customer satisfaction of selected telecommunication firms in Nigeria. The study employed quantitative method and survey research while the population for the study consisted ninety-four service team members selected from three (3) telecommunication firms with the largest number of subscribers in Nigeria. The sample size used for this study was total enumeration. The study employed a validated adapted questionnaire which was on a six-point likert-type scale and it was administered to the study participants to collect primary data. The reliability test of the questionnaire was achieved with Cronbach Alpha values was between 0.818 and 0.847. Data analysis and test of hypothesis was conducted with descriptive and inferential statistics. The result obtained from the analysis revealed that service scope has statistically positive and significant effect on market share of selected telecommunication firms in Nigeria (β = 0.515, t = 8.059, p<0.05). The study concluded that service quality affect customer satisfaction of selected telecommunication firms in Nigeria. It was recommended that firms should place more efforts in improving the quality of products and services in order to improve customer satisfaction and help reduce customer attrition.